2016
DOI: 10.1080/0886022x.2016.1209061
|View full text |Cite
|
Sign up to set email alerts
|

A novel factor for primary arteriovenous fistula failure: hyperinsulinism

Abstract: Introduction: Dysfunction of vascular access is an important reason of morbidity for dialysis patients and it is a major factor affecting the economical burden of hemodialysis. The preferred type of vascular access is creation of an arteriovenous fistula (AVF). However, the problem of fistula maturation rate is still a challenge. Herein, we tried to search the role of hyperinsulinism and insulin resistance as a new predictor of primary AVF failure (pAVFF) that may be a cause of intimal damage. Methods: We incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
4
2
0
Order By: Relevance
“…Other investigators showed that diabetic patients with AVF problems had a poorer homa-IR index (Homeostasis model assessment). Such metabolic disturbance may impair the vascular endothelium [7,31]. This is in line with the present study where the Cases with diabetic nephropathy had higher HbA1c values before intervention.…”
Section: Discussionsupporting
confidence: 90%
“…Other investigators showed that diabetic patients with AVF problems had a poorer homa-IR index (Homeostasis model assessment). Such metabolic disturbance may impair the vascular endothelium [7,31]. This is in line with the present study where the Cases with diabetic nephropathy had higher HbA1c values before intervention.…”
Section: Discussionsupporting
confidence: 90%
“…HD condition variables were strongly correlated to each other, so we chose to include only one -StKt/V associated with a worse metabolic control. Such metabolic disturbance may impair the vascular endothelium [11,43]. This is also in line with the present study where the Cases with diabetic nephropathy had higher HbA1c values before intervention, which thereafter improved and became similar to Controls.…”
Section: Discussionsupporting
confidence: 91%
“…17 However, there is a wide variation in the primary failure rates in the literature, 22.7%-53.5%. [21][22][23][24] We attribute our low primary failure rates of AVF (7.1%) to the routine pre-operative vascular mapping in the vascular department, which agrees with the recommendations of previous studies. 25,26 There was a strong correlation between peripheral arterial disease (for both AVF and AVG) and insertion site (for AVF) with increased primary failure rates.…”
Section: Discussionsupporting
confidence: 90%